2020
DOI: 10.4103/jfmpc.jfmpc_521_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of newly introduced foundation course for medical undergraduates: students' vs faculty's perspective

Abstract: Background and Objectives: In compliance with MCI's recommendation, a month-long Foundation Course was conducted in our institution in Aug’19. The present study was conducted to seek the opinion of the students and faculty regarding relevance of the topics included in the course to enable revisions to be made in designing the course for the subsequent sessions, to make it more effective and student-oriented. Methods: A questionnaire-based cross-sectional study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…Three previous studies have reported similar feedback from the students but the feedback has not been quantified in two of the studies. 10,12 In one of the studies however, 49% students felt the need to reduce the duration of the Foundation Course 8 which is in sharp contrast with only 7.57% respondents giving this feedback in our study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Three previous studies have reported similar feedback from the students but the feedback has not been quantified in two of the studies. 10,12 In one of the studies however, 49% students felt the need to reduce the duration of the Foundation Course 8 which is in sharp contrast with only 7.57% respondents giving this feedback in our study.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous studies have reported high level of appreciation for and satisfaction with the skills module sessions conducted during the Foundation Course. 8,10 Similarly, sessions on community orientation and field visits were perceived very positively by the students in a study conducted by Vyas S. et al 11 Few respondents recommended increasing the number of sessions on extracurricular activities and sports while two respondents felt that more types of sports should be included in the Foundation Course. Only 5 respondents (7.57%) felt that the duration of the Foundation Course should be reduced while 1 respondent pointed out the need to reduce repetition of topics between various sessions taken by different faculty members.…”
Section: Discussionmentioning
confidence: 97%
“…Where N is the sample size, Z is the z-value, p is the proportion of population, q is (1 -p), and d is the margin of error. For the purpose of the study p was taken as 0.5 (based on the study of Shah, Kulkarni, Arode and Singh in a Govt Medical College in Maharashtra) and margin of the error was kept at 5% [3]. Using the finite population correction, the sample size was worked out as 255 or more at a confidence level of 95%.…”
Section: Study Periodmentioning
confidence: 99%
“…A number of studies have also been undertaken to study the perception of the students about the course. Many considered it a welcome step by NMC, India to acclimatize the new MBBS students to the new professional environment [2,3]. Study carried out by Vyas, Joshi and Seth in a medical college in Ahmedabad, Gujrat revealed that the FC helped and prepared students to cope up with challenges of the MBBS course.…”
Section: Introductionmentioning
confidence: 99%